Menumbuhkembangkan Nilai-nilai Moral dalam Pembelajaran Pendidikan Agama Islam - Amrullah, Amrullah (LP3M STITNU AL HIKMAH MOJOKERTO, 2023)
This writing is talking about how learning Pendidikan Agama Islam (PAI) helps students build good character. PAI is an important part of teaching students about their religion and how to be good people. By learning about God, the Quran, Hadith, Islamic laws, history, and ethics in PAI lessons, students can become better individuals.